John Baldessari some stories (The National Gallery - A Private View, 1990)
Presented without commentary, this film reveals the thinking behind the work of John Baldessari over the course of his career, and provides clues to the understanding of the artist's paintings, photographic work and books. What emerges is a portrait of a thoughtful, quietly rebellious artist who has influenced a large number of younger artists over the last twenty years, and who has clearly followed his own path in the exploration of the territory which he embarked upon in the late 60's.